2012
DOI: 10.1097/opx.0b013e318255da73
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adequate Correction Following Vision Screening Failure

Abstract: Purpose To determine if compliance with referral one year after vision screening failure was associated with care model, demographic, or ocular factors. Methods Data were analyzed from 798 children in the Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) Study with habitual logMAR visual acuity (VA) ≥ 0.26 (20/40 +2 or worse) in either eye due to uncorrected or under-corrected refractive error and who returned the following year. The parents of 492 children failing in TX and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Amongst the quantitative studies, increasing age was associated with lower spectacle wear in four studies [11][12][13][14] whereas in two studies, in India and the USA, younger children were less compliant. 15,16 A study in China of school children who reported already owning spectacles, also reported compliance to be lower in younger children [ . A further study in India reported compliance to be highest in the youngest of three age groups but did not report complete statistics to support this.…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the quantitative studies, increasing age was associated with lower spectacle wear in four studies [11][12][13][14] whereas in two studies, in India and the USA, younger children were less compliant. 15,16 A study in China of school children who reported already owning spectacles, also reported compliance to be lower in younger children [ . A further study in India reported compliance to be highest in the youngest of three age groups but did not report complete statistics to support this.…”
Section: Agementioning
confidence: 99%
“…30 Uncorrected visual acuity and lines of improvement in visual acuity Seven studies reported higher compliance with lower levels of uncorrected visual acuity. 16,17,22,23,26,28,38 An eighth study reported compliance to be better with 'poor VA' compared to 'better VA', but no analyses were reported. 32 Two studies found no significant difference in compliance according to uncorrected visual acuity.…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…From the study sample, there were 239 emmetropes in grade 1. Data were missing for four students, and 43 students had RE (Hyperopia [ 3 ] + mild myopia [26], moderate myopia [ 1 ] and astigmatic myopia [ 13 ]). Of the 239 emmetropes in grade 1, there were 144 (60%) who remained emmetropic by grade 4.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] VA <6/18 due to RE is a predictor of poor compliance with spectacle wear. [ 13 ] Thus, better counseling of students and parents regarding the need for spectacles and continual use for overall development of the child could improve compliance.…”
Section: Discussionmentioning
confidence: 99%